FASN inhibitor TVB-3166 prevents S-acylation of the spike protein of human coronaviruses - Katrina Mekhail; Minhyoung Lee; Michael Sugiyama; Audrey Astori; Jonathan St-Germain; Elyse Latreille; Negar Khosraviani; Kuiru Wei; Zhijie Li; James Rini; Warren L. Lee; Costin Antonescu; et al. (Journal of Lipid Research, 2022)
The spike protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and other coronaviruses mediates host cell entry and is S-acylated on multiple phylogenetically conserved cysteine residues. Multiple protein acyltransferase enzymes have been reported to post-translationally modify spike proteins; however, strategies to exploit this modification are lacking. Using resin-assisted capture MS, we demonstrate that the spike protein is S-acylated in SARS-CoV-2-infected human and monkey epithelial cells. We further show that increased abundance of the acyltransferase ZDHHC5 associates with increased S-acylation of the spike protein, whereas ZDHHC5 knockout cells had a 40% reduction in the incorporation of an alkynyl-palmitate using click chemistry detection. We also found that the S-acylation of the spike protein is not limited to palmitate, as clickable versions of myristate and stearate were also labelled the protein. Yet, we observed that ZDHHC5 was only modified when incubated with alkyne-palmitate, suggesting it has specificity for this acyl-CoA, and that other ZDHHC enzymes may use additional fatty acids to modify the spike protein. Since multiple ZDHHC isoforms may modify the spike protein, we also examined the ability of the FASN inhibitor TVB-3166 to prevent S-acylation of the spike proteins of SARS-CoV-2 and human CoV-229E. We show that treating cells with TVB-3166 inhibited S-acylation of expressed spike proteins and attenuated the ability of SARS-CoV-2 and human CoV-229E to spread in vitro. Our findings further substantiate the necessity of CoV spike protein S-acylation and demonstrate that de novo fatty acid synthesis is critical for the proper S-acylation of the spike protein.